Giant left coronary artery diagonal branch left ventricular fistula: A case report and review of literature - Wang, Jingyue; Zhang, Huicong; Tong, Qian; Wang, Quanwei (Frontiers in Cardiovascular Medicine, 2022)
A 37-year-old Chinese man was admitted to the department of cardiology of the First Hospital of Jilin University for intermittent palpitation for 9 months, aggravating with chest pain for 3 days. After several examinations, he was diagnosed with giant left ventricular fistula of the diagonal branch of the left coronary artery. After routine treatment, which included improving circulation and administration of dual antiplatelet as well as hypolipidemic drugs among others, the patients' symptoms did not improve. The fistula was too big for transcatheter occlusion to be performed. A multi-disciplinary suggestion was that the patient be subjected to "surgical closure treatment"; however, for personal reasons, he refused the operation. After discharge, oral beta-blockers were prescribed for the patient. Incidences of congenital coronary arterial fistula in congenital cardiovascular disease are rare, and incidences of the giant fistula being located in the left heart system are even rarer. We report an adult male with a giant left anterior descending diagonal coronary artery left ventricular fistula and show various accessory examinations results. Non-invasive echocardiography was the first diagnostic option for the disease and pre-admission evaluation. Auxiliary diagnosis and exclusion value of cardiovascular magnetic resonance was revealed for the first time. The gold standard value of invasive coronary angiography (ICA) was proved again and it was also found that computed tomography angiography can be used instead of ICA for determining the exact relationships among anatomic structures. Furthermore, we performed a literature review on diagnosis and treatment of patients with this condition.